Risk analysis of brucelosis in the state of Tlaxcala - Guillermina García-Juárez; J Efrén Ramírez-Bribiesca; Maricela Hernández-Vázquez; Luz Marina Hernández-Calva; Efrén Díaz-Aparicio; Hermila Orozco-Bolaños (Instituto Nacional de Salud Pública, 2014)
Objective. To identify the risk of brucellosis in the state of Tlaxcala, Mexico. Materials and methods. A diagnosis of social type was conducted in the municipalities of Huamantla, Ixtenco and Teacalco, located in the eastern region of the state. The seroprevalence of brucellosis in goats and humans was determined. Results. 46.9% of producers know the programs of vaccination against brucellosis; 19.7% apply the vaccine and 80.3% do not apply the vaccine. Huamantla had the highest seroprevalence of animal brucellosis in 66.8%; San Jose Teacalco distributes unpasteurized cheeses to a distance of 270 km, increasing the risk of infection with brucellosis. Ixtenco recorded the highest prevalence of brucellosis in humans, with 1.51%. Conclusion. The municipalities studied present risks of infection and spread of brucellosis.